RETHINKING WALI ADHAL PROCEEDINGS: THE ROLE OF AUDI ET ALTERAM PARTEM IN ADVANCING PROCEDURAL FAIRNESS - Imron Rosyadi; Mohamad Asep (Faculty of Law, Universitas Diponegoro, 2025)
This study analyzes the procedural reconstruction of wali adhal cases in Indonesian Religious Courts, which are currently resolved through voluntary petitions (voluntair). In practice, a guardian who refuses without legitimate grounds is replaced by a judicial guardian (wali hakim) through a court decree; however, this procedure undermines procedural fairness by excluding the guardian's formal right to present objections. The research employs a normative juridical methodology, utilizing both legislative and conceptual approaches. The legislative approach critically examines the statutory regulations governing wali adhal cases, particularly the Marriage Law and the Compilation of Islamic Law. The conceptual approach is used to propose a procedural shift from voluntair to contentiosa, grounded in the principle of audi et alteram partem, which requires equal opportunities for all parties to be heard. Such reclassification is expected to ensure balanced judicial outcomes, protect the bride’s right to marry, and proportionately safeguard the guardian’s legal position. This study contributes to the development of more equitable judicial procedures within Religious Courts, ensuring procedural justice for both parties involved in wali adhal cases. The proposed shift would foster fairness in the legal process, allowing both the guardian and the bride equal legal standing, evidence presentation, and the right to challenge decisions, ultimately enhancing the legitimacy and fairness of judicial decisions.